Smart IOT Based Application to Reduce Car Accident - Zamri, Muhammad Izzat (IRC, 2020)
Road accident are still steadily increasing over years. On year 2017 to 2018 the death count on road accident have reach 5000 per year. The impact of the road accident varied from light injuries, severe injuries or even fatal. This will also lead to damage of property such as the vehicles. There are many factors contributing to the accident and can be categorised into several groups. One factor contributed to this is lack sight of incoming traffic when overtake a vehicles on a rural road. This paper proposed a solution to this issue by providing signal to the vehicles behind after processing and scanning the incoming vehicles using deep learning and image processing technique. The application will be testes in small-scale prototype to fully evaluate the application on the actual scenarios. It is to encourage road safety and ultimately reduce road accidents.